PEMBENTUKAN KARAKTER TOKOH MA KUN DALAM NOVEL TOKYO TAW? OKAN TO BOKU TO TOKIDOKI OTON KARYA NAKAGAWA MASAYA - Ayu Pertiwi Pendet, Ni Komang (Humanis, 2016)
The title of this thesis is “Character building in Ma kun figures in Tokyo Taw? Okan to Boku to Tokidoki Oton novel written by Nakagawa Masaya”. The result of this research based on psychoanalysis theory is the balance of Id, Ego, and Superego. Id has role on the main character to leave the villages. Ego is controling the id, the last is superego that gives limitation of act in accordance with moral norms. This research also finds six phases moral development in Ma kun figures, and each phase is a process of character building. The first phase (1) punishment and obedience orientation, character formed is the sunao “subservient”. The second phase (2) individualism and purpose, character formed is the hitonami “being average”. The third phase (3) interpersonal norms, character formed is the shitsuke “upbringing”. The forth phase (4) social system morality, character formed is the meiyo “keep honor”. The fifth phase (5) social contract, character formed is the ch?gi “devotion”. The sixth phase (6) universal ethical principle, and character formed is the hitome “public gaze”.
Keywords: psychology literature, moral development, character building